Peran Dan Tanggung Jawab Dishub (Dllajr) Dalam Penegakan Undang-Undang Nomor 22 Tahun 2009 Lalu Lintas Dan Angkutan Jalan - Widawati, Ayu; , Muchamad Iksan, SH, M.Hum (2016)
This study aims to determine the role of the Department of Transportation and the implementation of the enforcement of Law No. 22 of 2009 on Traffic and Road Force and to identify any obstacles and solutions to overcome these obstacles. This research method is a kind of juridical empirical legal research. Sources of data obtained from secondary data source of primary law, secondary and tertiary. Data were collected through the study of literature. Data analysis technique used is the analysis of qualitative data with an inductive method. Based on the results of this study concluded that, the role of the Department of Transportation Sukoharjo in the enforcement of Law No. 22 Year 2009 regarding Traffic and Road Transportation is a technical implementation legislation that is in accordance with the legislation in force and the authority under regional autonomy stipulated in Sukoharjo District Regulation No. 11 Year 2011 on the Implementation of Traffic and Transportation. Barriers faced by the Department of Transportation Sukoharjo in the prosecution of traffic violations, which should be the facilitation and coordination of the Police so that its authority be overlapping. Often in doing enforcement of traffic violations on the road along with the police, the Department of Transportation only as a police escort led to his role to be a minority.